Effects of radiant cooling on thermal comfort in energy commission building in Putrajaya, Malaysia - Al-Jazaari, Saaeed A. Neama (2013)
This study presents the effects of radiant cooling on thermal comfort conditions in Energy Commission Building, Malaysia. Which is also known as The Diamond Building located in Putrajaya. It is equipped with radiant slab cooling. The main objective of this study was to determine the effects of radiant cooling on office workers’ thermal comfort conditions. The survey procedure was adopted from the ASHRAE 55 and the ISO 7730 standards. Survey questionnaire were administrated to office workers in the second and sixth floors. The data were analyzed through comparison with ISO 7730’s thermal environment evaluation requirements. In total, 132 data sets completed by 49 participants were collected. The data were collected continuously for four days (two days for each floor) during working hours. The survey data is comprised of two groups. The first group is the result of two online questionnaires, namely a background survey and a daily survey. The second group is comprised of three measurements namely the indoor climate, the radiant asymmetry, and the meteorology. Findings of the thermal monitoring data suggests most of the thermal comfort conditions indices (excluding overall thermal comfort conditions) are within the recommended limits of the thermal comfort conditions standard of ISO 7730. However, the participants dissatisfied with the overall thermal environment. This dependent variable was compared with all of the independent variables in the background and daily surveys (personal variables, expectation, preferences, relative humidity, sweating, and head covering). The,result was a high correlation with preferences for increased air speed (p < .01),additional fans (p < .01), and more fresh air (p < .05). Moreover, a high indoor relative humidity is recorded (due to not using dew sensor). A regression was found between sweating and comfort (p < .01). Another finding suggests that participants (males and females) who wore a head covering felt warmer than those who did not wear a head covering (p < .01). In conclusion, radiant cooling is not the main cause of thermal discomfort conditions in this building. However, the air supply, the relative humidity, the sweating, and head covering were the main cause of thermal discomfort conditions in this radiant cooling environment.